Evaluation of anticaries activity of selected mouthwash marketed in Nigeria (2010)
Purpose: This work was aimed at evaluating four brands of mouthwash marketed in Nigeria for their anticaries activity. Method: The susceptibility pattern of bacterial isolates obtained from 30 patients having carious teeth to the selected mouthwash was determined using the cup-plate method. The zones of inhibition produced by the mouthwash against the bacterial isolates were measured to determine the degree of susceptibility. Results: The organisms isolated from the patients were Staphylococccus aureus, Klebsiella sp, Streptococcus sp, Escherichia coli and Pseudomonas aeruginosa in the following proportions: 30, 27, 20, 17 and 7 %, respectively. Anticaries evaluation revealed that 0.047 % thymol in ethanol displayed the highest degree of anticaries activity against all the Streptococcal species tested. Incorporation of preservatives in mouthwashes may adversely affect their anticaries activity as indicated by the fact that the preserved mouthwash exhibited lower activity than the unpreserved mouthwash. Conclusion: Anticaries activity is optimally achieved by using appropriate mouthwash combinations as this prevents both the initiation and progression of dental caries. The use of preservatives in mouthwash formulations should be done with caution as this may interfere with mouthwash activity.